Combining immunotherapy with radiation therapy in thoracic oncology - Badiyan, Shahed N.; Roach, Michael C.; Chuong, Michael D.; Rice, Stephanie R.; Onyeuku, Nasarachi E.; Remick, Jill; Chilukuri, Srinivas; Glass, Erica; Mohindra, Pranshu; Simone II, Charles B. (Journal of Thoracic Disease; Vol 10, Supplement 21 (August 09, 2018): Journal of Thoracic Disease (Advances in Radiation Oncology for Thoracic Malignancies), 2018)
Thoracic malignancies comprise some of the most common and deadly cancers. Immunotherapies have been proven to improve survival outcomes for patients with advanced non-small cell lung cancer (NSCLC) and show great potential for patients with other thoracic malignancies. Radiation therapy (RT), an established and effective treatment for thoracic cancers, has acted synergistically with immunotherapies in preclinical studies. Ongoing clinical trials are exploring the clinical benefits of combining RT with immunotherapies and the optimal manner in which to deliver these complementary treatments.